Recurrent Cerebral Amyloid Angiopathy–Related Hemorrhage. Issue 2 (March 2015) - Xu, Qingsheng; Fang, Mingwei; Feng, Yiping
<x xml:space="preserve">Abstract</x> Abstract Cerebral amyloid angiopathy is an important cause of intracerebral hemorrhage in normotensive elder individuals. Surgical treatment for cerebral hematoma due to amyloid angiopathy remains controversial, and some authors emphasized the difficulty of hemostasis during surgery and the risk of recurrent hemorrhage after surgery. A case study of a 68-year-old man with cerebral amyloid angiopathy and recurrent intracerebral hemorrhages is presented.